2006
DOI: 10.1007/s10811-006-9084-0
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Radionuclides (134Cs, 85Sr, 226Ra, 241Am) by Extracted Biomasses of Cyanobacteria (Nostoc Carneum, N. Insulare, Oscillatoria Geminata and Spirulina Laxis-Sima) and Phaeophyceae (Laminaria Digitata and L. Japonica; Waste Products from Alginate Production) at Different pH

Abstract: The extracted biomasses of four cyanobacteria (Nostoc carneum, Nostoc insulare, Oscillatoria geminata, and Spirulina laxissima) grown in axenic mass cultures, and of four samples of Laminaria obtained from different locations (L. digitata I and II, France; L. japonica I and II, China; all waste products from alginate production) were tested for their ability to adsorb four radionuclides ( 134 Cs, 85 Sr, 226 Ra, and 241 Am) under different pH regimes. In addition, two of the cyanobacterial biomasses (N. carneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Biosorption of heavy metal ions in wastewater using algae can offer an ecologically safer, cheaper, and more efficient means to remove metal ions from wastewater. Indeed algae can be used for sorption of toxic and radioactive metal ions [17], and also to recover precious metal ions like gold and silver [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Biosorption of heavy metal ions in wastewater using algae can offer an ecologically safer, cheaper, and more efficient means to remove metal ions from wastewater. Indeed algae can be used for sorption of toxic and radioactive metal ions [17], and also to recover precious metal ions like gold and silver [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…24 Several organisms able to trap Sr and/or Ba have been discovered, including some bacteria, micro-algae and plants. 11,[25][26][27][28][29][30][31][32][33][34][35] Different mechanisms of sequestration may be involved. First, Sr 2+ and Ba 2+ may be adsorbed on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…In algae, the brown alga Laminaria digitata adsorbed more than 80 % of 134 Cs under high pH conditions when the membrane was phosphorylated artificially (Pohl and Schimmack 2006). In this study, we found that the eustigmatophycean alga nak 9 could eliminate more than 90 % of radioactive Cs without any special treatment (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…PCC6803, an extracellular hemolysin-like protein (HLP) conjugate with polysaccharides functions to adsorb 109 Cd very rapidly (in a minute-order time course) (Sakiyama et al 2011). In N. commune , the absorption of 85 Sr into the cells is increased by phosphorylation on the cell surface (Pohl and Schimmack 2006). In terrestrial plants, sunflower is able to entirely absorb 150 μg Sr in 100 h when grown in radio-polluted water (Dushenkov et al 1997).…”
Section: Discussionmentioning
confidence: 99%